2022
DOI: 10.1021/acsami.2c02503
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Production of Reactive Oxygen Species with Zn2GeO4:Cu Nanorod-Loaded Microneedles for Methicillin-Resistant Staphylococcus Aureus Infectious Wound Healing

Abstract: Skin wound infection caused by methicillin-resistant Staphylococcus aureus (MRSA) is an urgent concern. Photodynamic therapy has emerged as a promising means of combating bacterial infection. However, continuous or repeated in situ light excitation is required for photosensitizers to produce reactive oxygen species (ROS), and most photosensitizers need sufficient oxygen to produce singlet oxygen ( 1 O 2 ), which greatly limits their clinical application. In this work, we report the preparation of Zn 2 GeO 4 :C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…For example, Yan et al. incorporated the photosensitizer Zn 2 GeO 4 :Cu 2+ (ZGC) into dissolving MNs [ 108 ]. The prepared MNs penetrated biofilms in a minimally invasive manner and delivered pre-UV-treated ZGC to infected wounds.…”
Section: Mns For Istrmentioning
confidence: 99%
“…For example, Yan et al. incorporated the photosensitizer Zn 2 GeO 4 :Cu 2+ (ZGC) into dissolving MNs [ 108 ]. The prepared MNs penetrated biofilms in a minimally invasive manner and delivered pre-UV-treated ZGC to infected wounds.…”
Section: Mns For Istrmentioning
confidence: 99%
“…Antibacterial agents involve antibiotics, natural extracts, cationic polymers, antimicrobial peptides, , and antibacterial materials. Most of them are not able to pass through the biofilm barriers efficiently, thus limiting their efficacies in the therapy of biofilm-associated infection. Mature biofilms act as barriers to antimicrobial agents by restricting their diffusion and preventing them from penetrating deeply into the matrix. Thus, novel therapeutic agents and strategies capable of fully accessing inside bacteria by penetrating the biofilm barriers for tackling biofilms are urgently needed . It was reported that molecules carrying positive charges would demonstrate comparably stronger biofilm penetration than neutral or negatively charged molecules. Wang and co-workers designed a guanidinium-functionalized pillar arene with a high antibacterial efficacy to disrupt biofilms .…”
Section: Introductionmentioning
confidence: 99%
“…33−35 Thus, novel therapeutic agents and strategies capable of fully accessing inside bacteria by penetrating the biofilm barriers for tackling biofilms are urgently needed. 36 was reported that molecules carrying positive charges would demonstrate comparably stronger biofilm penetration than neutral or negatively charged molecules. 37−40 Wang and coworkers designed a guanidinium-functionalized pillar 5 arene with a high antibacterial efficacy to disrupt biofilms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Different methods such as fluorescence, luminescence, and electrochemical methods have been developed for ROS detection. Among them, electrochemical methods exhibit advantages including good sensitivity, reliable reproducibility, short response time, and easy miniaturization .…”
mentioning
confidence: 99%